ANATOMICAL, MORPHOGENIC AND STRUCTURAL CHARACTERISTICS OF XARAÉS PALISADE GRASS UNDER GRAZING - Basso, Kelen Cristina; Galzerano, Leandro; DA SILVA, Wilton Ladeira; Ruggieri, Ana Cláudia [UNESP]; Reis, Ricardo Andrade [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2023)
This study evaluated under grazing intensities and periods of the year: leaf anatomy of Urochloa brizantha cv. Xaraés and its correlation with morphogenetic and structural characteristics, and leaves degradation after in situ incubation. Treatments were four grazing intensities (GI) defined by the pasture residuals leaf area index (rLAI 0.8, 1.3, 1.8, and 2.3) with three replications in a completely randomized design. Cows grazed in a rotational stocking with pastures regrowth period determined by 95% light interception. Leaves showed a higher proportion of sclerenchyma (2.64%) in pastures under lower GI and in the dry season (2.42%). Pastures managed under higher GI showed lower number of expanded leaves (2.58), lower number of lives leaves (3.45), and lower leaf senescence rate (0.05 cm tiller−1 d−1). Positive correlation was observed between leaf elongation rate and adaxial epidermis and vascular tissues. rLAI 1.8 and 2.3 provided greater residues after in situ leaf incubation at times 12, 48, 72, and 96 h compared to rLAI 0.8 and 1.3. rLAI and period of the year had little influence on leaf anatomy of the Xaraés managed under 95% LI, and leaf anatomy is correlated with the morphogenetic and structural pasture characteristics. Pastures managed under lower GI show more residues after leaves incubation in rumen.
Keywords: Light interception; Microscopy; Rumen incubation; Urochloa